PROBLEMS OF JUDICIAL ACTS REVIEW IN THE SUPREME COURT OF THE REPUBLIC OF KAZAKHSTAN - Ablaeva Эльвира Бекболатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The work is devoted to studying the problems of reviewing court decisions of lower courts by the Supreme Court of the Republic of Kazakhstan. This article examines the control of higher courts over lower courts’ activities in the system to ensure the rule of law in case consideration and decision-making. The procedure of reviewing judicial decisions by a higher court that have become effective and those that are not effective in the order of cassation and supervisory review, as well as representations of the President of the Supreme Court, and protests of the Prosecutor General of Kazakhstan, are investigated. Problems of citizens’ implementation of their constitutional rights to judicial protection and appeals against court decisions are highlighted. The grounds for reviewing judicial acts that have entered into force, the range of subjects entitled to apply for review, criteria for the admissibility of appealing judicial acts as well as procedure for preliminary consideration of complaints and protest by a judge alone is shown. The analysis of these issues allows us to conclude that the current grounds and procedure for reviewing judicial decisions of the appeal and cassation courts based on the submissions of the Chairman of the Supreme Court and the Attorney General of the Republic of Kazakhstan firstly hinder the realization of citizens’ constitutional right to judicial protection, including the right to appeal against judicial decisions, and secondly prevent the formation of consistency in judicial practice. The lack of guidance to lower courts on reviewing judicial decisions by way of cassation and supervision has once again convinced courts of their inability to achieve consistency in the interpretation and application of law, as well as failure to contribute effectively to citizens’ exercise of the right to justice. The paper provides a critical analysis of judges, lawyers, and legal experts on the current process for the Supreme Court of the Republic of Kazakhstan to review appeals and cassation court decisions. At the end of the paper, the author draws conclusions and makes suggestions regarding the enhancement of the constitutional right to judicial protection and uniformity in court practice.